2009
DOI: 10.1159/000214860
|View full text |Cite
|
Sign up to set email alerts
|

Schneckenbecken Dysplasia in Fetus: Report of Four Cases

Abstract: Several different types of lethal short-limbed skeletal dysplasia with platyspondylia have been recognized with a different mode of inheritance. Schneckenbecken dysplasia, a very rare lethal osteochondrodysplasia, is included in these entities, with an autosomal recessive mode of inheritance. We describe 4 new Tunisian cases with clinical, radiographic and histopathological features. The fetuses were of consanguineous parents. Prenatal diagnostics of short limbs were carried out on ultrasounds at 20, 22, 23 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The most asymmetrically expressed novel gene in the animal blastomeres, Slc35d1 , is implicated in the human disease Schneckenbecken dysplasia ( Borochowitz et al, 1986 ), considered to be associated with a dwarfism phenotype ( Lahmar-Boufaroua et al, 2009 ). To explore the importance of this gene in X. tropicalis during early development we injected a translation blocking morpholino oligonucleotide at different concentrations ( Section 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most asymmetrically expressed novel gene in the animal blastomeres, Slc35d1 , is implicated in the human disease Schneckenbecken dysplasia ( Borochowitz et al, 1986 ), considered to be associated with a dwarfism phenotype ( Lahmar-Boufaroua et al, 2009 ). To explore the importance of this gene in X. tropicalis during early development we injected a translation blocking morpholino oligonucleotide at different concentrations ( Section 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, 2 points should be considered here. First, our review of the literature showed that early midtrimester cases of the former 2 entities did not exhibit strikingly large barbell-like metaphyses [27,28,39]. Additionally, although the early midtrimester cases of Blomstrand dysplasia we identified did show enlarged metaphyses, the predominant findings were the markedly increased bone density and the thickened ribs [26].…”
Section: Discussionmentioning
confidence: 99%
“…Early midtrimester cases of Schneckenbecken dysplasia [39] and Torrance dysplasia [9], each reported at 20 weeks gestation, showed the expected short femora and humeri and platyspondyly. Our literature review did not identify early midtrimester cases of hypochondrogenesis or type 2 thanatophoric dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…SHNKND is severe lethal skeletal dysplasia which is characterized by a snail‐like pelvis, flattening of vertebral bodies, short and broad long bones with a dumbbell‐like appearance, hook‐shaped clavicles, hypoplastic scapulae, and thoracic hypoplasia. Clinical features of SHNKND patients are micromelic dwarfism, relative macrocephaly, flat midface, cleft palate, short neck, narrow chest, short ribs, brachydactyly, polyhydramnios (Borochowitz et al, 1986; Lahmar‐Boufaroua et al, 2009; Nikkels et al, 2001). All of the patients reported so far were stillborn or lethal in the neonatal period.…”
Section: Introductionmentioning
confidence: 99%
“…narrow chest, short ribs, brachydactyly, polyhydramnios (Borochowitz et al, 1986;Lahmar-Boufaroua et al, 2009;Nikkels et al, 2001). All of the patients reported so far were stillborn or lethal in the neonatal period.…”
mentioning
confidence: 99%